A proposed checklist for climate-friendly sport and exercise programmes. (26th August 2022) - Abu-Omar, Karim; Messing, Sven; Tcymbal, Antonina; Fleuren, Tobias; Richardson, Diana; Whiting, Stephen; Gelius, Peter; Wickramasinghe, Kremlin
Abstract: Background: Fighting the climate crisis is the greatest challenge of our time and will touch all aspects of people's lives. In this context, the United Nations (UN) have called on the sport sector to reduce its negative impacts on the environment and show 'climate leadership'. While some efforts have already been made with regards to mega sport events, there is still a dearth of approaches on limiting the climate impact of recreational sport and exercise programmes. Methods: Based on the UN-Framework 'Sports for Climate Action', literature reviews and additional desk research, a checklist to support local level stakeholders in providing climate-friendly sport and exercise programmes was developed. Results: The proposed checklist consists of five dimensions that need to be considered when designing and offering a climate-friendly sport and exercise programme: (i) active transport to exercise programmes, (ii) the carbon footprint of different types of exercises, (iii) low carbon sport clothing and equipment, (iv) instructors as champions for climate action and (v) advertising and communication. These five dimensions result in a 16-item checklist that supports the planning, advertising, implementation and evaluation of climate-friendly sport and exercise programmes. Conclusions: The proposed checklist intends to facilitate the development of climate-friendly sport and exercise programmes. However, additional work is needed to test the implementation of the checklist at the local level. While the sport sector can make its own contributions to reduce its climate impact, intersectoral action is needed to improve infrastructure for active transport and to build sustainable sport facilities.